2016
DOI: 10.2739/kurumemedj.ms65005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surgical Procedures for T2 Gallbladder Cancer in Terms of Recurrence and Prognosis

Abstract: Summary: T2 (tumor invades perimuscular connective tissue; no extension beyond serosa or into liver) gallbladder cancer has generally been treated by S4aS5 subsegmentectomy (S4aS5 HR). We investigated the therapeutic effect of full-thickness cholecystectomy (FC) and gallbladder bed resection (GBR), in terms of tumor location and resection margin (distance from the tumor). At our department we employ the following protocol to determine the extent of resection needed to achieve R0 status: (1) A tumor located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
1
7
0
2
Order By: Relevance
“…1b). Plenty of studies have indicated that the performance of radical resection might be the best choice for GBC management at clinical stage II [14,17,[22][23][24][25]. In our study, we also found that radical resection should be the only Fig.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…1b). Plenty of studies have indicated that the performance of radical resection might be the best choice for GBC management at clinical stage II [14,17,[22][23][24][25]. In our study, we also found that radical resection should be the only Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Since liver resection has been verified to have a poor survival outcome, with a 13~18% in-hospital mortality, [12,13], the effect of radical surgery for GBC patients at advanced stages with poor conditions is quite limited. Kawahara et al also have reported an effective surgical strategy for extent of resection in GBC at T2 stage, which is based on the gallbladder location of tumor [14].…”
Section: Introductionmentioning
confidence: 99%
“…Many GBCAs are diagnosed after simple cholecystectomy because the laparoscopic approach had become the golden standard treatment modality for gallbladder diseases. Current guidelines and studies recommend re-operation in incidental T2 GBCA because of residual cancer and survival bene t. 4,9,[15][16][17] However, real clinical situations are much different from guidelines. In many studies, reoperation rate or liver resection rate are lower than those that we expected.…”
Section: Discussionmentioning
confidence: 99%
“…However, Sternby et al contended that those studies constituted a low level of evidence because they involved a limited number of cases, they were exclusively retrospective observational studies and case reports, and they did not discuss the impact that lesions on the peritoneal or hepatic side of the gallbladder had on prognosis. In March 2017, Kawahara et al (5) published a retrospective study of 22 patients who underwent surgery for T2 GBC. The authors performed different surgical procedures based on the location of the lesion: full-thickness cholecystectomy (FC) + local lymph node dissection if a lesion of the gallbladder fundus or corpus is on the peritoneal side of the gallbladder (P-type) [author's note: this is T2a] ; gallbladder bed resection (GBR) + local lymph node dissection if the lesion is on the hepatic side of the gallbladder (H type) [author's note: this is T2b]; GBR + extrahepatic bile duct resection + local lymph node dissection if the lesion is on the cystic duct (N type).…”
Section: Current Status Of S4b+5 Resectionmentioning
confidence: 99%
“…(3) stones larger than 2 cm; (4) fully filled stones; (5) gallbladder wall calcification, porcelain gallbladder, with a malignancy rate as high as 50%; (6) thickening of the gallbladder wall; (7) atrophic gallbladder; (8) gallbladder adenoma or stones with gallbladder polypoid lesions; (9) gallbladder polyps larger than 1 cm; (10) preoperative MRCP suggesting an abnormality in the juncture of the bile and pancreatic ducts; (11) Mirizzi syndrome; (12) previous gallbladder ostomy (27); and (13) in China, patients who have undergone gallbladder-preserving micro-blasting lithotripsy should also be included.…”
Section: Preoperative Evaluation: Screening For High-risk Patients Wimentioning
confidence: 99%